2011
DOI: 10.1055/s-0031-1288918
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Reconstruction of the Auricle: Indications, Techniques, and Results

Abstract: Extensive defects of the ear require satisfactory cosmetic reconstruction to enable the patient to achieve full social integration. Although surgical procedures are the gold standard for reconstruction of the ear, in some cases they cannot be performed because of extended scars, threatening tumor, or congenital tissue abnormalities. Prosthetic reconstruction of the auricle is an established and reliable alternative technique to autologous surgical reconstructions. Since studies performed by Brånemark, osseoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…27 In contrast, there were no implant failures (0/65) in the 27 nonirradiated patients. Prior head and neck irradiation is not a contraindication for maxillofacial implant osseointegration in patients with cancer; 24,28 however, there is controversy regarding how best to preoperatively optimize these patients. 29 The highest survival rates for implants in irradiated extraoral applications are in the temporal bone, where the densely corticated and well-vascularized bone ensures a robust bone-implant interface to support functional loading.…”
Section: Zuo and Wilkesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In contrast, there were no implant failures (0/65) in the 27 nonirradiated patients. Prior head and neck irradiation is not a contraindication for maxillofacial implant osseointegration in patients with cancer; 24,28 however, there is controversy regarding how best to preoperatively optimize these patients. 29 The highest survival rates for implants in irradiated extraoral applications are in the temporal bone, where the densely corticated and well-vascularized bone ensures a robust bone-implant interface to support functional loading.…”
Section: Zuo and Wilkesmentioning
confidence: 99%
“…A delay period of 6 to 18 months after irradiation may permit soft tissue and bony healing stabilization before osseointegration surgery. 28 The use of a radiation shield to protect anticipated prosthetic sites has also been described. 18,33 A systematic review of temporal bone osseointegrated implants by Granström 30 in 2003 found that implant survival is high in irradiated patients up to 5 years postoperatively, after which time failures are common.…”
Section: Zuo and Wilkesmentioning
confidence: 99%
“…Local skin infection around the fixture could occur, as could the formation of granulation tissue and keloids. These are complications that can be avoided or resolved using appropriate medication and topical treatments without loss of the fixture [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Throughout history, materials such as silver, leather, porcelain, paper-mache, gelatin, latex, and acrylic were employed in prosthetic reconstruction. 24,25 Development of an ideal facial prosthetic relies on factors such as durability, flexibility, weight, color matching, longevity, biocompatibility, texture, hygiene, and thermal conductivity. 26 Modern materials used for head and neck prostheses are divided into methacrylates, polyurethane elastomers, and silicone elastomers.…”
Section: Methodsmentioning
confidence: 99%